8H-, 10H-, 14H-SiC formation in 6H-3C silicon carbide phase transitions - Vlaskina, S.I.; Mishinova, G.N.; Vlaskin, V.I.; Rodionov, V.E.; Svechnikov, G.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
In this paper the results of photoluminescence researches devoted to phase
transitions in 6H-3C-SiC have been presented. High pure 6H-SiC crystals grown by
Tairov’s method with and without polytype joint before and after plastic deformation at
high temperature annealing were investigated using optical spectroscopy. Low
temperature photoluminescence changes in the transition phase of SiC crystal represented
with the stalking fault spectra within the temperature range 4.2 to 35 K. The stalking
fault spectra indicate formation of metastable nanostructures in SiC crystals (14H₁
<4334>, 10H₂ <55>, 14H₂ <77>). The phononless part of each stalking fault spectrum
consists of two components of radiative recombination that are responsible for hexagonal
and cubic arrangement of atoms. Each of radiative recombination components in the
stalking fault spectrum has the width of entire band 34 meV and shifts relative to each
other by 26 meV. The overlap area of those components equals to 8 meV. The super-fine
structure of the recombination components in spectrum is observed, and it is related to
different Si – Si or C – C and Si – C bonds. Behavior of all the stalking fault spectra is
similar (temperature, decay of luminescence). The processes of the phase transition are
explained by the mechanism of interfacial rearrangements in the SiC crystals.